The correlation between knowledge, body image perception and self efficacy with anxiety among perimenopausal women in Dauh Puri Klod Village, Bali - Ni Made Ayu Yulia Raswati Teja; Ni Komang Ekawati; Ni Made Swasti Wulanyani (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: Level of anxiety among women approaching menopause is often high. This is influenced by knowledge, education, culture and customs, body image perception and self-efficacy. This study aims to determine the relationship between knowledge, perception of body image and self-efficacy with anxiety in perimenopausal women. Methods: This study employed a cross sectional design with 87 perimenopausal women aged 45-55 years in Dauh Puri Klod Village, Denpasar City, Bali Province. Respondents were selected with systematic random sampling from 1,039 women aged 45-55 years recorded in Dauh Puri Klod Village. Interviews were conducted at each respondent’s house in August 2018. Data collected included sociodemographic characteristics, knowledge, perception of body image, self-efficacy and anxiety levels among women approaching menopause. Bivariate analysis with chi square test and multivariate analysis with logistic regression were conducted to identify the association between variables. Results: The results of bivariate analysis showed that variables associated with anxiety were knowledge (p=0.001), perception of body image (p=0.012) and self-efficacy (p=0.001). The results of multivariate analysis with the backward method showed that the variables associated with anxiety were knowledge (AOR=10.83; 95%CI: 3.31-35.37) and self-efficacy (AOR=3.48; 95%CI: 1.09-11.14). Conclusion: Knowledge and self-efficacy have a significant association with anxiety in perimenopausal women. Various efforts to increase knowledge and to build self-efficacy are needed, such as an educational and support program to reduce anxiety in women approaching menopause.